Retinal degeneration in autoimmune polyglandular syndrome type 1: a case series. Issue 11 (29th April 2015) - Bourgault, Serge; Baril, Catherine; Vincent, Ajoy; Héon, Elise; Ali, Asim; MacDonald, Ian; Lueder, Gregg T; Colleaux, Kevin M; Laliberté, Isabelle
Abstract : Background: Autoimmune polyglandular syndrome type 1 (APS1) is a rare autosomal recessive disorder due to mutations in the AIRE gene. Aim: To report the ocular features and characterise the retinal phenotype in molecularly confirmed APS1. Method: This retrospective case series reviewed five molecularly confirmed cases with APS1 known to have ocular involvement (age range: 19 months–44 years; mean follow-up of 8 years). The medical history, ocular history and evaluation, visual field testing, full-field electroretinogram (ERG) and antiretinal antibody results were reviewed. Results: All but one case had decreased vision at first presentation. All cases had peripheral pigmentary retinal changes; macular atrophy was noted in 80% of cases. The most common feature on spectral-domain optical coherence tomography was a disruption of the external limiting membrane and inner segment ellipsoid band (n=3). Fundus autofluorescence imaging demonstrated a parafoveal ring of hyper-autofluorescence (n=1) or a stippled and patchy autofluorescence pattern in the macula (n=1). The visual fields were constricted in all tested patients (n=3). The rod ERG was abnormal in all cases; the relative involvement of rods and cones differed. Four patients who were tested for antiretinal antibodies were found positive by immunohistochemistry (n=3) and/or western blot (n=2). Conclusions: Photoreceptor degeneration is part of APS1 phenotype and the presence of antiretinal antibodies strongly supports an aetiology similar to that of non-paraneoplastic autoimmune retinopathy. Periodic retinal evaluation and imaging, visual field testing and ERG would assist in monitoring the retinopathy in APS1-related disease.